Self-assembly of iron oxide precursor micelles driven by magnetic stirring time in sol–gel coatings. Issue 31 (4th June 2019) - López-Sánchez, J.; Serrano, A.; Campo, A. del; Abuín, M.; Salas-Colera, E.; Muñoz-Noval, A.; Castro, G. R.; Figuera, J. de la; Marco, J. F.; Marín, P.; Carmona, N.; Rodríguez de la Fuente, O.
Abstract : Sol–gel synthesis of self-assembled iron oxide precursor micelles. Abstract : The purpose of this work is to fabricate self-assembled microstructures by the sol–gel method and study the morphological, structural and compositional dependence of ε-Fe2 O3 nanoparticles embedded in silica when glycerol (GLY) and cetyl-trimethylammonium bromide (CTAB) are added as steric agents simultaneously. The combined action of a polyalcohol and a surfactant significantly modifies the morphology of the sample giving rise to a different microstructure in each of the studied cases (1, 3 and 7 days of magnetic stirring time). This is due to the fact that the addition of these two compounds leads to a considerable increase in gelation time as GLY can interact with the alkoxide group on the surface of the iron oxide precursor micelle and/or be incorporated into the hydrophilic chains of CTAB. This last effect causes the iron oxide precursor micelles to be interconnected forming aggregates whose size and structure depend on the magnetic stirring time of the sol–gel synthetic route. In this paper, crystalline structure, composition, purity and morphology of the sol–gel coatings densified at 960 °C are examined. Emphasis is placed on the nominal percentage of the different iron oxides found in the samples and on the morphological and structural differences. This work implies the possibility of patterning ε-Fe2 O3 nanoparticles in coatings and controlling their purity by an easy one-pot sol–gel method.